The study of the association between the job satisfaction and commitment among the employees at Felda Engineering Services Sdn. Bhd. / Zaitulfadhilah Samsudin - Samsudin, Zaitulfadhilah (2003)
Job satisfaction and commitment may influence the way an organization stands. Workers are important assets to determine the successfulness of predetermine objectives of such organizations. So, it is essential to undergo studies and research about the relationship between job satisfaction and commitment. It may discover some problems and from that we can search for the solutions and recommendations, where appropriate. Organization also can determine factors that can satisfy an employee and what makes them committed in their carriers. This study was done at Felda Engineering Services Sdn Bhd among employees in Kuala Lumpur. Questionnaires are one of approaches to collect information and later analyzed by Statistical Package for Social Sciences (SPSS). The finding is hopefully can contribute to help Felda in order to upgrade their job satisfaction and commitment among employees.